2022
DOI: 10.28991/cej-2022-08-09-014
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Types of Bracing System and Shear Wall on the Seismic Response of RC Buildings Resting on Sloped Terrain

Abstract: Several factors have been affecting the urban design areas, leading to the construction of reinforced concrete (RC) buildings. Buildings on sloped terrains have been gaining increased popularity, especially from architectural peers. The vulnerability of constructions to seismic loads on sloped terrains increases due to mass and vertical irregularity, which in turn increases the torsional moments as well as shear forces. To control the effect of the seismic loads, many systems have been implemented, including s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
0
1
1
Order By: Relevance
“…Therefore, it is clear that the interaction between the soil and the structure, as well as the choice of bracing system, are significant factors that must be considered in the design and construction of buildings. A recent study has shown that bracing with shear walls reduces displacement, which is not contradictory to our findings [43]. Neglecting these factors can lead to significant increases in lateral displacement, potentially compromising the stability and safety of the building.…”
Section: Lateral Displacementcontrasting
confidence: 61%
See 1 more Smart Citation
“…Therefore, it is clear that the interaction between the soil and the structure, as well as the choice of bracing system, are significant factors that must be considered in the design and construction of buildings. A recent study has shown that bracing with shear walls reduces displacement, which is not contradictory to our findings [43]. Neglecting these factors can lead to significant increases in lateral displacement, potentially compromising the stability and safety of the building.…”
Section: Lateral Displacementcontrasting
confidence: 61%
“…This indicates that shear wall bracing is more effective in reducing the time period of the structure. This was demonstrated in another recent study, which showed that the use of shear wall bracing leads to a reduction in fundamental time period values by between 22.29% and 24.93% for the various levels of the models studied [43]. Hence, it is crucial to consider the bracing type during the design phase to ensure that the structure can withstand seismic forces efficiently.…”
Section: Time Periodmentioning
confidence: 80%